Marketing for competitiveness : Asia to the world! in the age of digital consumers - Kotler, Philip; Kartajaya, Hermawan, 1947-; Hooi, Den Huan (Singapore : World Scientific, 2017)
Asia is the most populated geographical region, with 50% of the world's inhabitants living there. Coupled that with the impressive economic growth rates in many Asian countries, the region provides a very attractive and lucrative market for many businesses, big and small and from all industries. In addition, Asia is also a dynamic market that significantly grows with developments in technology and digitalization. For example, a research by Google and Temasek shows that Southeast Asia is the world's fastest growing internet region. The internet economy in Southeast Asia is expected to grow by 6.5 times from US$31 billion in 2015 to US$197 billion in 2025. All these make it critical for marketers, whether domestic, regional or global, to stay in touch if not ahead, in their understanding of what is happening in Asia from a marketing perspective and what Asia has to offer to the world. One phenomenon happening in the Asian market and which marketers should pay utmost attention to, is the rapidly unfolding digital revolution that has fundamentally transformed not just the extent but also the nature of competition. What makes it even more challenging and complicating is also how such a revolution impacts on consumer and business buying behavior. Disruptive technologies supported by this digital revolution have brought in new competitors and enabled existing competitors to surpass the conventional boundaries which we may be quite familiar with. Asian consumers have become more educated and connected and have embraced newer ways of selecting, buying and using products and services. In this book, the Father of Modern Marketing, Professor Philip Kotler has collaborated with two marketing experts from Asia, Hermawan Kartajaya from Indonesia and Hooi Den Huan from Singapore to publish a book on Marketing for Competitiveness: Asia to the World In the Age of Digital Consumers. This book argues that marketing is no longer just vertical but has encompassed a new, more horizontal paradigm. In addition to many new concepts and frameworks, this book includes a plethora of real-world examples from various countries in Asia, which will help to shed light on how companies, both Asian and global, compete in Asia. Useful lessons can be drawn by all businesses in the world on how to win the mind, heart and spirit of the Asian consumer digital and non-digital. --Amazon.com.
Preface : the anatomy of change. Technology as the primary driver -- Political-legal, economy, and social culture as the main drivers -- Market as the ultimate driver -- Part I. Marketing is transforming? Competitive landscape : the dynamic arena. Product-centric perspective : connectivity in product development -- Customer-centric perspective : connecting with the digital consumer -- Human-centric perspective : doing good by doing well in the connected world -- Part II. Marketing is moving? Competitive position : the core essence. Being strategy : from positioning to confirmation -- Core tactic : from differentiation to codification -- Value indicator : from brand to character -- Part III. Marketing is creating? Competitive marketing : the whole set -- Marketing strategy for value exploration -- Marketing tactic for value engagement -- Marketing value with values -- Postface: Glorecalization mindset : Asia to the world! Asia's local champions -- Asia's regional players : Asia vision, local actions -- Asia's multinational companies : global value, regional strategy, local tactics.
Includes bibliographical references.
Keywords: Marketing -- Asia; Internet marketing -- Asia